Factors of prevalence of subclinical mastitis in dairy cows in the district of Florida, Amazonas Region, Peru - Alvarado C., Wigoberto (2019)
The aim of this study was to determine the main factors that influence the prevalence of subclinical mastitis in Florida, Amazonas Region, Peru. Fifty cows under hand-milking of 15 farms were used. The prevalence of subclinical mastitis was determined by the California Mastitis Test (CMT) and the DCC Test (DeLaval Direct Cell Counter). Milking routines were observed to determine the main prevalence factors. Data analysis was performed using contingency tables, the chi-square test and bivariate correlations. The prevalence of subclinical mastitis according to the DCC method was 52% and by CMT was 51%, without significant differences between methods. The main factors that influenced the prevalence of subclinical mastitis were due to poor hygiene practices and inadequate facilities.